Management of Brass Instrument A case study of E-Sarn Trombone Ensemble - Jantarajaturaphat, Pitikiat (Journal of Music and Performing Arts Khon Kaen University, 2023)
The purpose of this article is to study and present the management of the I-San Trombone Ensemble was established in 2022 with the primary goal of performing at concerts at the Thailand, Trombone International 2022 before it became a long-term plan to advance the musician’s skills. There is a small band management that emphasizes how to participate in a remote area context, Defined goals, rehearsal management and concert performances, The I-San Trombone Ensemble Band has a lot of obstacles that pose a great challenge to all members. Both in the matter of joining a band that has a short period, together with different musical skills. In which this is an example case study that occurred within the scope of a group of students who are members of the band. The establishment of I-San Trombone Ensemble is considered a band that takes time for the development of knowledge in many things which over time will allow various knowledge to be crystallized and can be used to further develop musical skills.